Gamma radiation induced synthesis and optical characterization of cobalt and nickel nanoparticles stabilized in polymer - Ilias, Suhaila Hani (2011)
An attempt was made to synthesize Cobalt (Co) and Nickel (Ni) nanoparticles by radiation induction method with polyvinyl alcohol (PVA) and polyvinyl pyrrolidone (PVP) used as capping agents. Metal precursors CoCl2 and NiSO4 at various concentrations together with deionized water, polymer capping agent, and ascorbic acid anti-oxidant were stirred homogenously for 6 hours and the solutions were irradiated with 60Co gamma rays at various doses up to 50 kGy. Free electrons and hydrated electrons generated by  radiation interaction with water interacts with cobalt ions Co+ and nickel ions Ni2+ reduced them into Co and Ni zero valent atoms. After aggregation of atoms, metal nanoparticles are formed. The irradiated solutions containing PVA/Co nanoparticles, PVP/Co nanoparticles, PVA/Ni nanoparticles, and PVP/Ni nanoparticles were characterized for their size, shape, optical and electronic structures. The average particle sizes were measured by photon cross correlation spectroscopy which shows that the particle size was influenced by the precursor concentration and absorbed dose. The transmission electron micrographs were used to determine the particle structural morphology. The average particle diameter decreases with an increase of dose and a decrease of precursor concentration. The effect of PVA and PVP on the particle sizes is not very significant for the formation of Co and Ni nanoparticles. The UV-Visible spectrophotometer measurements revealed the formation of metal nanoparticles by exhibiting the absorption peak max at about 520 and 400 nm for Co and Ni nanoparticles respectively. The absorption energy is referred as the conduction band energy determined from the absorption peak max by ECB = hc/max. For a given precursor concentration the absorption peak max blue shifts redundant with the increase of dose, indicating the conduction band of Co and Ni nanoparticles increases as the dose increases. The conduction band for Co nanoparticles in PVA increased from 2.416 eV at 10 kGy to 2.440 eV at 50 kGy for 1.0% wt CoCl2 and from 2.398 eV at 10 kGy to 2.421 eV at 50 kGy for 3.0% wt CoCl2. For Ni nanoparticles in PVA, the conduction band increased from 3.160 eV at 10 kGy to 3.184 eV at 50 kGy for 1.0% wt NiSO4 and from 3.120 eV at 10 kGy to 3.152 eV at 50 Gy for 3.0% wt NiSO4. The conduction band has a large energy value at the smaller particle sizes with an increase of dose. An increase of the conduction band with a decrease in particle size confirmed the phenomenon of quantum confinement effect for Co and Ni nanoparticles.